183k views
4 votes
Y=-2x
Y=-4x+6
Solve each system by substitution

1 Answer

0 votes

y = -2x

y = -4x + 6. Set the equations equal to each other because they both equal y.

-2x = -4x + 6. Add 4x to each side.

2x = 6. Divide each side by 2.

x = 3. Substitute 3 for x in one of the first equations to get the y value.

y = -2(3)

y = -6.

To ensure these are the correct numbers, let's plug -6 and 3 back into one of the equations.

-6 = -2(3)

-6 = -6

x = 3 and y= -6 are correct.

User Saran Banerjee
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.